Effects of the non-steroidal anti-inflammatory drug(NSAID) naproxen on gene expression of antioxidant enzymes in zebrafish (Danio rerio) - Stancová, V; Ziková, A; Svobodová, Z; Kloas, W (Environmental toxicology and pharmacology, 2015)
The aim of this study was to investigate the effects of naproxen on the gene expression of antioxidant enzymes in adult zebrafish. Surprisingly, after 2 weeks exposure no significant effect on the mRNA expression of the target genes was found in the liver. However, mRNA levels of three genes were altered significantly in the intestine. The expression of Ucp-2 decreased at the environmental concentration of 1μg/L while mRNA expression of GST p2 increased at the concentration of 100μg/L. The mRNA level for the antioxidant enzyme CAT was up-regulated significantly at both the concentrations used. Exposure to naproxen caused only moderate effects on the expression of antioxidant genes in the intestine rather than in the liver, which demonstrates that the intestine is more sensitive to waterborne naproxen exposure than the liver. Interestingly, the adverse side effects of NSAIDs occur in the gastrointestinal tract of humans. To our knowledge, this is the first study that has focused on transcriptional effects of naproxen on zebrafish.
Keywords: Zebrafish; glutathiontransferasa; antioxidancia; střeva; proteiny dánia pruhovaného; Zebrafish Proteins; Fish; Naproxen; Glutathione Transferase; Oxidative stress; Gene Expression Regulation, Enzymologic; mRNA expression; dánio pruhované; iontové kanály; Uncoupling Protein 2; mitochondriální proteiny; Catalase; Anti-Inflammatory Agents, Non-Steroidal; Ion Channels; antiflogistika nesteroidní; Mitochondrial Proteins; Animals; játra; Antioxidants; regulace genové exprese enzymů; zvířata; katalasa; Intestines; Liver; naproxen; uncoupling protein 2